Typification of seven names in the genus Antirrhinum (tribe Antirrhineae, Plantaginaceae) - Ferrer-Gallego, P. Pablo; Fabado, Javier; Güemes, Jaime (Phytotaxa, 2021)
The typification of seven names in the genus Antirrhinum (tribe Antirrhineae, Plantaginaceae): A. charidemi, A. latifolium, A. molle var. mollissimum, A. molle var. marianum, A. sempervirens, A. siculum, and A. valentinum is discussed. The designation of the nomenclatural types is based on the consultation of original material and the literature cited in the respective protologues. The names are lectotypified using specimens from BC, C, MA, and an illustration of Boccone published in 1697. An epitype is also designated for A. latifolium due to ambiguity in the interpretation of the lectotype. The name A. siculum is neotypified from a specimen preserved at VAL, and a second-step lectotypification is applied for the names A. sempervirens and A. valentinum. Finally, a comment on the nomenclatural type of A. cirrhigerum is reported.